Transplantation of kidneys from hepatitis C‐positive donors into hepatitis C virus‐infected recipients followed by early initiation of direct acting antiviral therapy: a single‐center retrospective study. (2nd May 2017) - Bhamidimarri, Kalyan R.; Ladino, Marco; Pedraza, Fernando; Guerra, Giselle; Mattiazzi, Adela; Chen, Linda; Ciancio, Gaetano; Kupin, Warren; Martin, Paul; Burke, George; Roth, David
Summary: The availability of direct acting antiviral agents (DAA) has transformed the treatment of hepatitis C virus (HCV) infection. The current study is a case series that reports the outcomes from a cohort of twenty‐five HCV‐infected ESRD patients who received a kidney from an anti‐HCV‐positive deceased organ donor followed by treatment with DAAs in the early post‐transplant period. Time to transplantation and the efficacy of DAA therapy as measured by sustained viral response at 12 weeks were assessed. The median waiting time from original date of activation on the United Network Organ Sharing (UNOS) waiting list until transplantation was 427 days; however, the median time from entering the patient into UNet sm for a HCV‐positive offer until transplantation was only 58 days. The 25 patients were started on antiviral treatment early post‐transplant (median 125 days) and 24 of 25 (96%) achieved a sustained virologic response at 12 weeks. Tacrolimus dose adjustments were required during antiviral treatment in 13 patients to maintain therapeutic levels. Accepting a kidney from an anti‐HCV‐positive deceased donor shortened the waiting time for HCV‐infected kidney transplant candidates. We recommend that kidneys from anti‐HCV‐positive donors should be considered for transplant into HCV‐infected recipients followed by early post‐transplant treatment with DAA agents.